Socio-demographic Characteristics of Drowning Cases Recorded At a Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: The autopsy diagnosis of drowning represents one of the major problems in forensic medicine. Objective: The purpose of the present study was to see the socio-economic characteristics of the drowning cases. Methodology: It was a retrospective study of 20 cases of drowning in 13 thanas of Dinajpur district during 1st January 2004 to December 2006. All the cases were autopsied in the mortuary of Dinajpur Medical College, Dinajpur. All the above may show signs of immersion on examination. Result: Total 20 cases were brought to the Department of Forensic Medicine at Dinajpur Medical College, Dinajpur. Considering the socio-economic status of the victim, it is found that higher frequency of drowning in the lower socio-economic growth. Highest age group is present in the 0-10 years which is 4 cases, 5 cases and 4 cases in the year of 2004, 2005 and 2006 respectively. Conclusion: In the conclusion, the study reveals that majority drowning cases are from low socio-economic condition with an early age group. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14418 J Shaheed Suhrawardy Med Coll, 2012;4(2):57-59